33rd Bled eConference – Enabling Technology for a Sustainable Society: June 28 – 29, 2020, On-line Conference Proceedings (University of Maribor Press, 2020)
The Bled eConference, organized by the University of Maribor, Faculty of Organizational Sciences, has been shaping electronic interactions since 1988. The Bled eConference is the oldest, most traditional and well renowned conference in the field with a tradition of more than 30 years. In 2020, for the first time in history, Bled eConference was held online due to COVID-19 pandemic. The role of digital technologies has never been as important as in this time, enabling people to interact and work from home during quarantine. The theme of this year’s 33rd conference is “Enabling Technology for a Sustainable Society”. In the context of the digital society, the implementation of digital technologies to achieve higher efficiency and competitive advantage is insufficient. Society calls for different economy models which need to be more responsible, righteous and less exploitative to achieve wellbeing of all and sustainable development of society. Digital technologies have an important role to achieve these goals. In this year’s conference, we address various aspects of digital transformation opportunities and challenges. We provide directions and guidelines for organizations to meet and overcome these challenges on their way towards designing sustainable business models. Themes covered in the papers of these proceedings are focused on: business model innovation; big data, data science; e-health, digital wellness; new applications and organizational models; and novel approaches and cases for education in the digital economy.